2012
DOI: 10.1371/journal.pone.0033902
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Impact of Atrial Fibrillation in Patients with Pulmonary Hypertension

Abstract: BackgroundPulmonary hypertension (PH) is associated with progressive impairment of right ventricular function, reduced exercise capacity and a poor prognosis. Little is known about the prevalence, clinical manifestation and impact of atrial fibrillation (AF) on cardiac function in PH.MethodsIn a four year single-centre retrospective analysis 225 patients with confirmed PH of various origins were enrolled to investigate the prevalence of AF, and to assess the clinical manifestation, 6-minute walk distance, NT-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
68
2
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(79 citation statements)
references
References 25 publications
5
68
2
4
Order By: Relevance
“…Further parameters known to be increased in patients with PH and arrhythmias are RAP and PVR [5,8,9]. Interestingly, in our study, RAP in patients who developed AF during follow-up (7 ± 5 vs. 5 ± 4 mm Hg) was lower than in other studies.…”
Section: Discussioncontrasting
confidence: 72%
See 2 more Smart Citations
“…Further parameters known to be increased in patients with PH and arrhythmias are RAP and PVR [5,8,9]. Interestingly, in our study, RAP in patients who developed AF during follow-up (7 ± 5 vs. 5 ± 4 mm Hg) was lower than in other studies.…”
Section: Discussioncontrasting
confidence: 72%
“…Mean survival time was shorter in patients with AF but this effect was not statistically significant. Rottlaender's et al study [8] revealed reduced TAPSE in patients with evidence of AF. These results are consistent with our study, which found reduced TAPSE in patients with AF in baseline ECG (15 ± 5 mm) compared with those with SR in the baseline ECG (18 ± 5 mm).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Частота ФП у пациентов с легочной гипертензи-ей составляет 31,1% (в 41,3% случаев пароксиз-мальная и в 58,7% случаев -постоянная форма ФП). Отмечена связь между ФП и дилатацией правых камер сердца [9,18,19]. В нашем исследовании получены ас-социации ЛГ с наджелудочковыми аритмиями и ЖЭ, а также установлены взаимосвязи между дилатацией ПП и ФП, между дилатацией ПЖ и ФП, а также ЖЭ.…”
Section: Discussionunclassified
“…A study performed by Mielniczuk et al (22) showed that the consequence of higher right atrial pressure is reduced renal function. Another recently published study evaluated several echocardiographic parameters in a population with pulmonary hypertension (23). The group with the larger right atrial area suffered from significantly reduced renal function, although it has to be mentioned that this result might not be a causal relationship (23).…”
Section: Discussionmentioning
confidence: 99%